The Role of Micro, Small and Medium Enterprises in Improving the Local Economy in Rumbuk Village, Sakra District, East Lombok Regency - Nurmuliyani, Nurmuliyani; Emi Salmah (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
This study aims to analyze the role of Micro, Small, and Medium Enterprises (MSMEs) in enhancing the local economy in Rumbuk Village, Sakra Subdistrict, East Lombok Regency. MSMEs play a significant role in creating employment opportunities, increasing community income, and driving village economic growth. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The results show that MSMEs have a positive impact on the local economy, particularly in reducing unemployment and improving community welfare. However, MSME actors still face several challenges, such as limited capital, market access, and lack of skills training. Therefore, support from the government and relevant institutions is essential to improve the capacity and sustainability of MSMEs in the region. Overall, MSMEs play a strategic role in strengthening the local economic structure and supporting sustainable rural development.